A 1.2 kilometer walk of fame or shame ? the level of satisfaction of Iloilo Esplanade users - Agocejos, Ma. Romylen (University of the Philippines Visayas, 2013)
Nowadays, public spaces have beome a significant part of the lives of the people in towns and cities. Project for Public spaces (PPS) proposed a set of principles that contributes to a succesful public space. The four key qualities that make a public space successful are : access and linkage, comfort and image, uses and activities, and sociability. However, studies previously related to satisfaction of public spaces ( as in case with parks and sports and cultural facilities) are rare and are done mostly in more developed countries. This study aims to determine the levels of satisfaction of Iloilo esplanade users based on the four key qualities provided by the PPS. It further discusses the issues and concerns of Iloilo Esplanade users. Moreover, the study proposes the hypotheses that there are significant differences on the level of satisfaction of Iloilo esplanade users and their sex, age and time of the day. Survey was the major method used in this study wherein questionnaires were given to the respondents. Other methods of data gathering such as overt participant observation, use of photographs, and pagtatanung-tanong ere used to supplement results from the survey. SPSS was used to analyze quantitative data and thematic analysis was used for qualitative data. Statistical tests such as t-test, Scheffe test, ANOVA, Levene's test were used to analyze the data. The mean average rating of iloilo esplanande users based on the four key qualities fall between ranges of 3.8 to 4.4 which shows that people are only slightly satisfied on the access and linkage, comfort and image, uses and activities, and sociability of esplanade. Statistical tests showed that there is a significant difference on the level of satisfaction of Iloilo esplanade users among age groups in terms of sociability. meanwhile, statistical tests showed that there is no significant difference on the level of satisfaction of Iloilo esplanade users on the the other independent variables of this study, sex and time of the day in terms of the four key qualities. Ising photographs, the respondents were asked about their favorite spot in Esplanade and it was revealed that the bench on the middle part of the place is the most favorite of the majority. Overt participant observation and pagtatanung-tanong identified some of the issues and concerns of Iloilo Esplanane users.